1976
DOI: 10.1136/bmj.1.6020.1241
|View full text |Cite
|
Sign up to set email alerts
|

Extra-articular features in early rheumatoid disease.

Abstract: One hundred and two patients who presented with rheumatoid disease within the first year of onset were studied prospectively every four months for a mean 4-5 years to assess the incidence of extra-articular features. The features that seemed to be common in the early stages included hand-muscle wasting, carpal tunnel syndrome, lymphadenopathy, non-specific ankle swelling, and rheumatoid nodules, and to a lesser extent hepatomegaly, being underweight, conjunctivitis, skin transparency, and a palpable thyroid gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 6 publications
0
26
1
1
Order By: Relevance
“…In our RA patients without any clinically observed neurological deficit, 6% demonstrated CTS and 18% MNM. These are much lower than the results of Fleming et al [8], who found median nerve entrapment in 52% of RA patients whose mean disease duration was 4.5 years. Lang et al [3] found manifest or subclinical mononeuropathies of the median nerve in five of their 23 RA patients.…”
Section: Discussioncontrasting
confidence: 74%
“…In our RA patients without any clinically observed neurological deficit, 6% demonstrated CTS and 18% MNM. These are much lower than the results of Fleming et al [8], who found median nerve entrapment in 52% of RA patients whose mean disease duration was 4.5 years. Lang et al [3] found manifest or subclinical mononeuropathies of the median nerve in five of their 23 RA patients.…”
Section: Discussioncontrasting
confidence: 74%
“…The prevalence of peripheral neuropathy and its related factors vary among previous studies, as shown in Table 5 [5,6,14,15,16]. Furthermore, it is difficult to compare studies examining peripheral neuropathy in RA because the inclusion criteria and neuropathy assessment methods varied between previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The material for this paper is taken from the Middlesex Hospital Prospective Study of Early (Fleming et al, 1975(Fleming et al, , 1976.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were divided into three prognostic categories on the basis of functional grade, extent of joint involvement, grip strength, and duration of early morning stiffness (Fleming et al, 1976). These categories were 'improved', 'mild', and 'severe', but for the purpose of this analysis the first two have been considered together as 'mild'.…”
Section: Methodsmentioning
confidence: 99%